Arahan dan Strategi Perlindungan Lahan Sawah Untuk Mendukung Ketahanan Pangan Di Kabupaten Maros, Sulawesi Selatan: Direction and Strategies for Protection of Rice Fields to Support Food Security in Maros Regency, South Sulawesi - Munawir, Munawir; Abdullah, Nuryahya; Ashari, Ahmad Firman (Universitas Hasanuddin, 2023)
Integration of Maros Regency into the KSN Mamminasata and the increasing population has increased the conversion of rice fields. This research aims to (a) Analyze conversion of rice fields in Maros Regency period 2013-2042 (b) Analyze status of food balance in Maros Regency period 2023-2042, and (c) Formulate directions and strategies for protecting rice fields to support food availability in Maros Regency. The method used is visual interpretation of spot 5 satelite in 2012 and 2022 to obtain data on rice fields. The trend of paddy field conversion was obtained using spatial analysis. Paddy field data for 2042 was obtained based on prediction results using the Artificial Neurol Network (ANN) model using Land Change Modeler (LCM) application. Status of food balance in Maros Regency is obtained from the area of paddy fields in 2022 and 2042. The protection of paddy fields is based on 3 scenarios, using the rational method. Formulation of directions and strategies using the A'WOT method. The results of this research showed that land conversion in Maros Regency for the 2013-2023 period was 1,946 ha or 7%, while the 2023-2042 period had increased to 3,722 ha or 15%. The status of land balance in Maros Regency is a deficit from 2022 to 2042. The area of paddy fields must be protected to provide local food availability at 4,940 ha. The strategy for protecting rice fields is a strategy to improve the quality of rice fields to increase productivity, and strengthening policies that are more consistent and consequential.